Elchems Card as An Innovative Learning Media Based on Augmented Reality (AR) on The Topic of Periodic Table of Elements - Risca Safitri Kurniawati; Tutik Sri Wahyuni (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2026)
In the Society 5.0 era, education is expected to contribute to achieving the Sustainable Development Goals (SDGs) through the integration of digital technology. Chemistry, especially the periodic table of elements, remains challenging for students because of its abstract nature, requiring both memorization and conceptual understanding. This study aims to develop a learning media in the form of chemical element picture cards based on augmented reality (AR) technology on the topic of the periodic table of elements, namely Elchems Card. The research and development method used a modified 4D Thiagarajan model comprising three stages: define, design, and develop. Data analysis techniques used both quantitative and qualitative descriptive methods. The developed product was subjected to a feasibility trial involving 33 students to assess its feasibility and collect student responses. The results show that the developed Elchems Card was rated as very good by material and media experts with an average score 95.8% and 96.8%, respectively, and received positive responses from students with an average score of 86.5%. This study was limited to the feasibility testing and student response stages and did not include effectiveness testing. It can be concluded that Elchems Card can be used as an innovative learning medium on the topic of the periodic table of elements. These findings indicate that Elchems Card not only enhances students’ motivation and engagement but also aligns with the digital transformation agenda in education. The media has the potential to be further developed for other chemistry topics.